2019
DOI: 10.1002/jbio.201960014
|View full text |Cite
|
Sign up to set email alerts
|

Safety of light emitting diode‐red light on human skin: Two randomized controlled trials

Abstract: Therapeutic applications of light emitting diode‐red light (LED‐RL) are expanding, yet data on its clinical effects are lacking. Our goal was to evaluate the safety of high fluence LED‐RL (≥160 J/cm2). In two phase I, single‐blind, dose escalation, randomized controlled trials, healthy subjects received LED‐RL or mock irradiation to the forearm thrice weekly for 3 weeks at fluences of 160‐640 J/cm2 for all skin types (STARS 1, n = 60) and at 480‐640 J/cm2 for non‐Hispanic Caucasians (STARS 2, n = 55). The prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Adverse events (AEs) included treatment-site erythema, hyperpigmentation, and blistering, all of which were mild and resolved without permanent sequelae [38]. We concluded that LED-RL is safe up to 480 J/cm 2 and may exert differential cutaneous effects depending on race and ethnicity, with darker skin being more photosensitive [38].…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Adverse events (AEs) included treatment-site erythema, hyperpigmentation, and blistering, all of which were mild and resolved without permanent sequelae [38]. We concluded that LED-RL is safe up to 480 J/cm 2 and may exert differential cutaneous effects depending on race and ethnicity, with darker skin being more photosensitive [38].…”
Section: Introductionmentioning
confidence: 92%
“…The LED-RL treatment device emitted visible red light (633 ± 6 nm) at a power density of 360.2 W/m 2 at room temperature and a distance of 10 mm from the skin surface [40,42]. The mock treatment device simulated the LED-RL treatment device (i.e., had the same physical components and thermal output) but did not emit red light [38]. The use of mock phototherapy controlled for environmental factors that may affect wound healing, such as ambient light and temperature [35].…”
Section: Treatment Devicesmentioning
confidence: 99%
See 3 more Smart Citations